A Cross-Industry Analysis of Financial Ratios: Comparability and Corporate Performance. - Mensah, Yaw M.; Moriarity, Shane R. (The Accounting Review, 1991)
Reviews the book `A Cross-Industry Analysis of Financial Rations: Comparability and Corporate Performance,' by J. Edward KEtz, Rajib K. Doogar and David E. Jensen.